ANALISIS DAMPAK PENERAPAN NILAI AL-ISLAM DAN KEMUHAMMADIYAHAN TERHADAP KASUS BULLYING PADA SANTRI/AH PESANTREN MODERN MUHAMMADIYAH KWALA MADU LANGKAT - A’yunina, Qurrota; Rahman, Abd (CV. Lafadz Jaya, 2025)
Bullying is a form of verbal and physical violence that continues to occur in educational environments, including Islamic boarding schools. This phenomenon contradicts the values of Islam and morality that should be instilled through student character development. This study aims to analyze the influence of implementing Islamic and Muhammadiyah values on bullying cases among students at the Muhammadiyah Modern Islamic Boarding School of Kwala Madu, Langkat. A quantitative approach was used, employing a survey method with questionnaires distributed to 287 respondents. Data analysis involved tests of validity, reliability, normality, linearity, Pearson correlation, and simple linear regression using statistical software. The results showed that all instrument items were valid and reliable, and the relationship between variables was linear. A strong and significant negative correlation was found between the implementation of Islamic and Muhammadiyah values and bullying behavior. The higher the internalization of these values, the lower the tendency for bullying among students. This study concludes that Islamic and Muhammadiyah values play a crucial role in shaping student character and serve as a strategic factor in preventing bullying in boarding schools effectively and sustainably.